(untitled) (Global Journal of Management and Business Research, 2012)
n the era of globalization, business environment becomes highly dynamic with high risk and uncertainty. This uncertainty decreases market share and increases organizational inefficiency. The increasing attention on human resource management (HRM) in small and medium enterprises (SMEs) is a comparatively recent phenomenon. HR-researchers have largely ignored the SMEs, even though smaller companies could be fruitful subjects for empirical investigation because of their numbers, the growth-rates and not least diversity in the qualitative aspects of management practices. Thereby HRM in SME#x2019;s has been a white spot on the map, and this despite the characteristic Pakistan industrial structure, i.e. the large proportion of SMEs; the long tradition for a rather institutionalized and well unorganized labor market, which could provide a basis for a more professional approach to human resources, and finally the supposed very good basis for future competitiveness, due to the values characterizing employees as well as managers in Pakistani companies, i.e. democratic management style,( A Democratic Management Style has moderate approach to a situation whether at work or in a social places. The way things are get done is to seek opinion from your staffs as opposed to giving a direct instruction.